2021
DOI: 10.1016/j.bjps.2020.08.033
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown and beyond: Home practice solutions for developing microsurgical skills.

Abstract: Correspondence and Communications COVID-19 lockdown and beyond: Home practice solutions for developing microsurgical skills. Dear Sir, Current COVID-19 restrictions present significant challenges to Plastic Surgery training. Numerous obstacles exist; including the necessity for social distancing, global PPE shortages, virtual clinics decreasing trainee exposure to pathology, reduced face-to-face clinical teaching, and limited time in theatre. 1 Furthermore, suspension of nonurgent elective reconstruction work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Many solutions for virtual skills training have been suggested, including at-home use of laparoscopic box trainers, immersive operative room simulation, and use of at-home suturing models. 23 , 24 , 25 At our institution, we utilized several of these innovative strategies to deliver skills-based curricula during our intern summer school. While additional investigation of the effect of this shift is ongoing, due to the significant changes between virtual and hands-on training in the skills aspect of our curriculum, we did not directly compare its effects in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many solutions for virtual skills training have been suggested, including at-home use of laparoscopic box trainers, immersive operative room simulation, and use of at-home suturing models. 23 , 24 , 25 At our institution, we utilized several of these innovative strategies to deliver skills-based curricula during our intern summer school. While additional investigation of the effect of this shift is ongoing, due to the significant changes between virtual and hands-on training in the skills aspect of our curriculum, we did not directly compare its effects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…While there are benefits to the shift to online learning including the ability to safely reach an increased number of learners, 12 the effects of this shift are still undergoing investigation. Modified didactic, 13 surgical skills, 14 , 15 and mock oral board examination 16 curricula were enacted at multiple centers demonstrating feasibility and resident satisfaction. Many educational formats have required significant restructuring in order to convert to a virtual setting, and thus direct comparison to the outcomes of previous, in-person formats is limited and the effectiveness of these new formats is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, the novel Coronavirus disease 2019 (COVID-19) has further presented significant challenges to microsurgical training, as cancellation of elective surgeries has reduced operative volume and trainees' time under an operating microscope. 7,8 In March 2020 alone, U.S. hospitals lost between 30 to 55% of elective surgical case volume. 9 In April 2020, a survey distributed to members of the American Council of Academic Plastic Surgeons showed that over 95% of respondents reported their institution had prohibited all elective surgery that month.…”
mentioning
confidence: 99%
“…Thus, despite a rapidly changing landscape, plastic surgeons have remained steadfast in the pursuit of excellent patient care, rigorous education, and the safety and longevity of the community. From embracing telehealth and virtual educational platforms to the use of 3-D printing in order to address shortages in personal protective equipment, 4 , 5 the plastic surgeon continues to adapt and innovate. Plastic surgery journals and their editorial teams have played an invaluable role in this process.…”
mentioning
confidence: 99%